PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA DAN PENGOLAHAN TANAMAN KELOR MENJADI TEH DAN LULUR HERBAL SEBAGAI OBAT TRADISIONAL - Sumardani, N.L.G.; Ratnaningsih, N.N.; Ardiani, N.L.Y.; Saraswati, I. A. P. W. S.; Kusumadewi, N. N. E. (Buletin Udayana Mengabdi, 2024)
Moringa oleifera Lam , commonly known as the moringa plant, is one type of traditional medicinal plant (known as TOGA) that offers numerous health benefits. The village of Songan B, located in the Kintamani sub-district of Bangli Regency, Bali Province, is a village known for its moringa plants, which are scattered across the Kintamani hills. These moringa plants have the potential for further development, including the processing of moringa into beneficial products for the community. The purpose of this initiative is to empower the local community of Songan B, Kintamani, to enhance their knowledge and skills regarding the cultivation and utilization of moringa plants. The aim is to transform the use of moringa from just a vegetable and livestock feed into processed products with higher market value, such as moringa leaf tea and moringa paste. This project was carried out through socialization and demonstrations on how to produce moringa leaf tea and moringa paste, as well as establishing demonstration plots for moringa seedlings. The project was successful, thanks to the strong support and appreciation from the community, leading to increased knowledge and skills among the people in processing moringa plants. As a result, they were able to produce moringa leaf tea and moringa paste that can be consumed by a wider population.